Diferentes densidades de Trichospilus diatreae (Hymenoptera: Eulophidae) e seu desenvolvimiento sobre pupas de Thyrinteina arnobia (Lepdoptera: Geometridae) - Zaché, Bruno [UNESP]; Zaché, R. R. da Costa [UNESP]; Wilcken, Carlos Frederico (My University, 2011)
The control of defoliating caterpillars in eucalyptus forests via the application of chemical and biological insecticides is a complex issue, mainly due to the large size of plantations and the height of trees. Because of this complexity, alternate control methods have been proposed, such as biological control. Several factors should be taken into consideration for biological control programs to be successful, including density of natural enemies released. In this experiment we used 48-hour-old Thyrinteina arnobia pupae exposed to parasitism by 48-hour-old Trichospilus diatraeae females at the following parasitoid/host ratios, respectively: 1:1, 7:1, 14:1, 21:1, 28:1, and 35:1, with 15 replicates per treatment. Density was an important factor for T. diatraeae development, since parasitism rates of 33.3% were found at a density of 1 female per pupa, while no significant differences were found among parasitism rates for densities of 7, 14, 21, 28, and 35 females/pupa, with parasitism rates above 70 %. As to emergence, densities of 1:1 and 35:1 did not differ statistically, with low emergence rates. The 7:1 density had an intermediate performance, while densities of 14:1, 21:1, and 28:1 were the most effective, with emergence rates above 90%. With regard to the number of emerged parasitoids there was a positive intraspecific interference up to the 28:1 density. There was an increase in development period from egg-adult as the density of females per pupa increased.
Trichospilus diatreae (Hymenoptera: Eulophidae) and its development on Thyrinteina arnobia pupa (Lepidoptera: Geometridae)